The effect of stimulation smart book educative game tool on improving fine motor skills for early childhood - Eva Oktaviani; Imawan Eko Setiyono (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: The COVID-19 pandemic has resulted in a global wave of crises that have a massive impact on all aspects of life. The world of education, especially learning activities, is also an impact that is in the spotlight. The change in learning activities from face-to-face to distance learning makes it difficult for early childhood education levels. Studies prove the impact of the Covid-19 pandemic on disorders of fine motor development in children aged 3-4 years with a high category of 60.71%. Early age is the golden age of rapid child development, so positive stimulation is needed for optimal growth and development. An important aspect that affects the overall development of children is fine motor skills. Fine motor skills can be developed through various fun activities through the smart book educational game tool.Objectives: The purpose of this study was to test the effectiveness of smart book educational game stimulation on fine motor skills in early childhood.Methods: This research was an action research with nonequivalent control group pretest-posttest design. Stimulation using smart books was carried out for five days with 90 minutes. The number of samples was 80 PAUD children, consisting of 40 children in the intervention group who were given smart book stimulation and 40 children in the control group without smart book stimulation only using conventional educational game tools that are usually done in everyday schools. Statistical test using general linear model + posthoc bonferroni.Results: The results showed that there was a significant effect on the fine motor skills of early childhood who were given smart book stimulation and those that were not given with a p value of 0.001.Conclusions: Educational game-based learning can be used to stimulate children's fine motor skills and is expected to be integrated into children's learning activities with various methods.